Concomitant immune-related events in Wilson disease: implications for monitoring chelator therapy - Seeßle, Jessica; Gotthardt, Daniel; Schäfer, Mark; Gohdes, Annina; Pfeiffenberger, Jan; Ferenci, Peter; Stremmel, Wolfgang; Weiss, Karl Heinz (Journal of inherited metabolic disease, 2016)
Current guidelines favor the use of chelating agents (d-penicillamine, trientine) in first line therapy of symptomatic Wilson disease patients. Development of chelator induced immunological adverse events are a concern especially under d-penicillamine therapy. This study assessed the prevalence of co-existing or therapy-related immune-mediated diseases in Wilson disease patients, and evaluated the role of antinuclear antibodies in therapy monitoring.
Published online: 12 June 2015
Gesehen am 27.05.2020